Risk of Introduction in Northern Vietnam of HPAI Viruses from China: Description, Patterns and Drivers of Illegal Poultry Trade. Issue 4 (30th September 2014) - Desvaux, S.; Nguyen, C. O.; Vu, D. T.; Henriquez, C.; Ky, V. D.; Roger, F.; Fenwick, S.; Goutard, F.
Summary: Poultry movement is known to contribute to the dissemination of highly pathogenic avian influenza (HPAI) viruses. In Northern Vietnam, the illegal trade of poultry from China is a source of concern and is considered as responsible for the regular introduction of new H5N1 viruses. The general objective of this study was to get a better understanding of this illegal trade (organization, volume, actors involved and drivers) to propose adequate preventive and control options. The information was also used to qualitatively evaluate the risk of exposure of susceptible poultry to HPAI H5N1 virus introduced from China by illegally traded poultry. We found that the main products imported from China are spent hens, day‐old chicks (DOCs) and ducklings; spent hens being introduced in very large number. The drivers of this trade are multiple: economic (especially for spent hens) but also technical (demand for improved genetic potential for DOC and ducklings). Furthermore, these introductions also meet a high consumer demand at certain periods of the year. We also found that spatial dispersion of a batch of poultry illegally introduced from China is extensive and rapid, making any prediction of possible new outbreaks very hazardous. Finally, a risk mitigation plan should include measures to tackle the drivers of this trade or to legally organize it, to limit the threat to the local poultry sector. It is also essential for traders to be progressively better organized and biosecure and for hygienic practices to be enforced, as our study confirmed that at‐risk behaviours are still very common among this profession.